2014
DOI: 10.1007/s12098-014-1587-0
|View full text |Cite
|
Sign up to set email alerts
|

CDC Kerala 15: Developmental Evaluation Clinic (2–10 y) – Developmental Diagnosis and Use of Home Intervention Package

Abstract: The experience of conducting the developmental evaluation clinic for children between 2 and 10 y has shown that a team consisting of developmental therapist, speech therapist, preschool teacher, special educator, clinical child psychologist and developmental pediatrician, using appropriate test results of the child could make a clinical diagnosis good enough for providing early intervention therapy using a home based intervention package.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A similar range of neurodevelopmental disorders have been found in similar CDC settings worldwide with involvement of multidisciplinary teams including developmental therapists, speech therapists, preschool teachers, special educators, clinical child psychologists and developmental pediatricians [16]. Previous studies of children with NDD have shown marked male preponderance (166/224), especially among those with either cognitive or language delay [17,18].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A similar range of neurodevelopmental disorders have been found in similar CDC settings worldwide with involvement of multidisciplinary teams including developmental therapists, speech therapists, preschool teachers, special educators, clinical child psychologists and developmental pediatricians [16]. Previous studies of children with NDD have shown marked male preponderance (166/224), especially among those with either cognitive or language delay [17,18].…”
Section: Discussionmentioning
confidence: 69%
“…Speech and language delay is one of the commonest NDD in preschool children in most populations [16]. The outpatient consultation for a child with speech and language delay often requires a multidisciplinary approach and should consist of a structured history, examination, and relevant targeted investigations with the aim of identifying whether the delay is primary or secondary in nature,.…”
Section: Discussionmentioning
confidence: 99%
“…An example of successful integration and maintenance of a service to assess developmental delay has been reported from the Isle of Wight [17]. Another example is a team assessment model for children 2-10 years of age from Kerala, India [18]. A scoping review found certain components facilitating sustainability of integrated behavioural healthcare: process-related issues, such as the role of interprofessional communication and implementation support; content-related issues, such as the use of clear protocols; and organizational issues, such as co-employment of the care providers [19].…”
Section: Introductionmentioning
confidence: 99%
“…These conditions stem from a variety of causes, leading to diverse clinical presentations based on the nature of the insults, often occurring in combinations. Symptoms include challenges in posture maintenance, gait, and rigidity or fatigue, along with low muscle tone in the limbs [4]. Associated problems may encompass different forms of learning disabilities, seizures, issues with feeding, growth, and impairments in vision and hearing.…”
Section: Introductionmentioning
confidence: 99%